IJRTP Volume 12(iii) Table of Contents - Taruna (The international journal of religious tourism and pilgrimage, 2024)
Special Issue: Papers Presented at International Conference on Religious Tourism (ICRT-2023), held at the Department of Management Studies, Babasaheb Bhimrao Ambedkar University Lucknow, (U.P), India, 27-28 March 2023